PENGEMBANGAN KETERAMPILAN GURU MELALUI PELATIHAN PENGELOLAAN MEDIA PEMASARAN BERBASIS DIGITAL - Laser Narindro; Rully Mardjono; Dimmas Mulya; Elfira Febriani Harahap (Abdimas Universal, 2021)
To make labor for the Business and Industrial Sectoral in the industrial era 4.0 requires educational institutions such as schools to fulfill entrepreneurial-based curriculum achievements through the Entrepreneurial Maker School program which has been targeted by the Government to support creating graduates who has the soul, knowledge and skills in marketing products using digital media. To support this, one of the efforts is through training on making web-based marketing applications and digital marketing strategies for this teacher for using CMS tools in the form of wordpress applications and marketing strategies using Google Adsense tools to provide the needed understanding and skills. The purpose of this skills training is to help teachers be able to have innovations in teaching and learning activities and make reference to teaching materials that are given to students in class. This community service activity partner is the 40 Jakarta State Vocational High School. The methods used are lectures in providing materials and skills training for teachers. As for 20.8% of respondents quite understand, 50% of respondents understand and 29.2% of respondents really understand the material provided during the skills training provided.